Association of Baseline and Longitudinal Changes in Body Composition Measures With Risk of Heart Failure and Myocardial Infarction in Type 2 Diabetes: Findings From the Look AHEAD Trial. Issue 25 (22nd December 2020) - Patel, Kershaw V.; Bahnson, Judy L.; Gaussoin, Sarah A.; Johnson, Karen C.; Pi-Sunyer, Xavier; White, Ursula; Olson, KayLoni L.; Bertoni, Alain G.; Kitzman, Dalane W.; Berry, Jarett D.; Pandey, Ambarish
Abstract : Background: Intentional weight loss is associated with lower risk of heart failure (HF) and atherosclerotic cardiovascular disease among patients with type 2 diabetes. However, the contribution of baseline measures and longitudinal changes in fat mass (FM), lean mass (LM), and waist circumference (WC) to the risk of HF and myocardial infarction (MI) in type 2 diabetes is not well established. Methods: Adults from the Look AHEAD trial (Action for Health in Diabetes) without prevalent HF were included. FM and LM were predicted using validated equations and compared with dual-energy x-ray absorptiometry measurements in a subgroup. Adjusted Cox models were used to evaluate the associations of baseline and longitudinal changes in FM, LM, and WC over 1- and 4-year follow-up with risk of overall HF, HF with preserved ejection fraction (EF; EF ≥50%), HF with reduced EF (EF <50%), and MI. Results: Among 5103 participants, there were 257 incident HF events over 12.4 years of follow-up. Predicted and measured FM/LM were highly correlated ( R 2 =0.87–0.90; n=1369). FM and LM decreased over 4-year follow-up with greater declines in the intensive lifestyle intervention arm. In adjusted analysis, baseline body composition measures were not significantly associated with HF risk. Decline in FM and WC, but not LM, over 1 year were each significantly associated with lower risk of overall HF (adjusted hazard ratio per 10% decrease in FM, 0.80 [95% CI, 0.68–0.95]; adjusted hazard ratio per 10% decrease in WC, 0.77 [95% CI, 0.62–0.95]). Decline in FM was significantly associated with lower risk of both HF subtypes. In contrast, decline in WC was significantly associated with lower risk of HF with preserved EF but not HF with reduced EF. Similar patterns of association were observed for 4-year changes in body composition and HF risk. Longitudinal changes in body composition were not significantly associated with risk of MI. Conclusions: In adults with type 2 diabetes, a lifestyle intervention is associated with significant loss of FM and LM. Declines in FM and WC, but not LM, were each significantly associated with lower risk of HF but not MI. Furthermore, decline in WC was significantly associated with lower risk of HF with preserved EF but not HF with reduced EF. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT00017953. Abstract : Supplemental Digital Content is available in the text.